3H-1,2-Benzoxaphosphepine 2-oxides as selective inhibitors of carbonic anhydrase IX and XII - Aleksandrs Pustenko; Anastasija Balašova; Alessio Nocentini; Claudiu T. Supuran; Raivis Žalubovskis (Taylor & Francis Group, 2023)
The synthesis of 3H-1,2-benzoxaphosphepine 2-oxides and evaluation of their inhibitory activity against human carbonic anhydrase (hCA) isoforms I, II, IX, and XII are described. The target compounds were obtained via a concise synthesis from commercial salicylaldehydes and displayed low to sub-micromolar inhibition levels against the tumour-associated isoforms hCA IX and XII. All obtained benzoxaphosphepine 2-oxides possess remarkable selectivity for inhibition of hCA IX/XII over the off-target cytosolic hCA isoforms I and II, whose inhibition may lead to side effects.